MUSYAWARAH KITAB: KEGIATAN PENGUATAN SOLIDARITAS ALA PESANTREN SYARIF HIDAYATULLAH KEPANJEN - Shofiadi, Muhammad Rizqi Abroor; Perguna, Luhung Achmad (Jurnal Ilmiah Sosiologi Agama (JISA), 2024)
The aim of this research is to analyze Islamic boarding school-style solidarity in book deliberation activities and determine the driving and inhibiting factors of Islamic boarding school-style solidarity in book deliberation activities at the Syarif Hidayatullah Kepanjen Islamic Boarding School. The research method used is a qualitative approach with descriptive methods. The informants in this research were the caretakers of the Syarif Hidayatullah Islamic Boarding School, supervisor of the book deliberation, chairman of the Committee Lajnah ad-Dirosah at-Tolabiyah, and two students. The informant selection technique used purposive sampling, data collection was carried out by observation, interviews and documentation. The data analysis technique uses the Miles Huberman model. This research was analyzed using Emile Durkheim's Social Solidarity theory. The results of the research show that (1) the forms of Islamic boarding school-style solidarity in book deliberation activities at the Syarif Hidayatullah Kepanjen Islamic Boarding School are mutual cooperation, togetherness, and tolerance. (2) The driving factors for Islamic boarding school-style solidarity in book deliberation activities are the same goals, the activeness of the students, and the collaboration of the students. (3) Furthermore, the factors inhibiting Islamic boarding school-style solidarity in book deliberation activities are the lack of active santri, the existence of conflicts that arise, and the lack of reciprocity from the management